Research on the sustainable development of winter sports from the perspective of cultural resources - Lyu, Shanshan; Jasmon, Abadan (Edelweiss Applied Science and Technology, 2026)
This paper discusses the sustainability of winter sports development in the long run, considering cultural resources as one of the main criteria, along with infrastructure and technology. The study combines Resource-Based Theory, Cultural Resource Theory, and Sustainable Development Theory to examine the effect of cultural resources on the sustainability of winter sports. The article uses survey data collected from 869 individuals, including winter sports fans, spectators, and organizers across different climatic regions in China, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that cultural resources have a significant impact on enhancing public participation (b = 0.629, p < 0.001) and directly influence the development process (b = 0.285, p < 0.001). The relationship between cultural resources and sustainability is mediated by public participation, which has a strong indirect effect (b = 0.229, p < 0.001). This association is further moderated by climatic conditions, with stronger effects in colder areas (b = 0.421) than in temperate ones (b = 0.198). The research presents a novel approach to winter sports management, emphasizing culturally and climate-sensitive strategies for sustainable development.